Evaluation of the ZIG-ZAIDS game: an entertaining educational tool for HIV/Aids prevention - Virgínia T. Schall; Simone Monteiro; Sandra M. Rebello; Maysa Torres
This article presents the evaluation process for the ZIG-ZAIDS game, investigating the material's applicability in formal and informal educational contexts, i.e., how the game has been used by health professionals, parents, and the target population (pre-adolescents, or children over 9 years old). The study involved evaluation questionnaires sent to a list of schools and institutions using the game, plus interviews and visits to places where the game was used as well as tested with groups of students. It also includes an analysis of evaluation previously sent by the authors to people who had requested the game. The results showed that the population's level of information is more relevant than age in relation to the game's impact. Another important aspect relates to ZIG-ZAIDS' applicability to different situations: training of health and teaching professionals; activities with street children; municipal institutions and events, schools, companies, communities, and health care centers. In summary, ZIG-ZAIDS was found to be an entertaining, creative, and innovative alternative for providing information on AIDS and sexuality.